Bernt Balchen : polar aviator - Glines, Carroll V (Smithsonian Institution Press, 1999)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Scott and Amundsen - Honda, Katuiti (The Asahi-Shinbun, 1999)
Publication Title: Complete collection of Katsuichi Honda
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

The Quest for the South Pole: Successes and Deaths - Feeney, Robert E (Polar journeys : the role of food and nutrition in early exploration, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ernæring; mat; oppdagelsesreiser

Dagboksnotater fra Sydpolen - Hassel, Sverre (Vågemot miniforl., 1997)
Publication Title: Sydpol-serien
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Into the heart of the Antarctic - Imbert, Bertrand C (North Pole, South Pole : journeys to the ends of the earth, 1992)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

The South Pole expedition 1910-1912 - Huntford, Roland (The Amundsen photographs, 1987)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Scott and Amundsen - Huntford, Roland (Hodder & Stoughton, 1979)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

The South Pole - Mountfield, David (A history of polar exploration, 1974)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Byrd's South Pole Flight - 1929-30 - Isakson, Evelyn Moore (Bernt Balchen, colonel, United states Air force, retired : a special report on the unique career of a great American patriot, 1972)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Amundsen triumphs - Quartermain, L B (South to the Pole : the early history of the Ross Sea sector, Antarctica, 1967)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

The first man at the South Pole - Victor, Paul-Emile; Sullivan, Scott (Man and the conquest of the poles, 1964)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpol; Sydpolsekspedisjonen; oppdagelsesreiser

The race to the South Pole - Andrist, Ralph K (Heroes of polar exploration, 1963)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

Kapløbet til Sydpolen - Kirwan, Laurence Patrick (Polarforskningens eventyr, 1963)
Keywords: Antarktis; Roald Amundsen; Sydpol; Sydpolsekspedisjonen; oppdagelsesreiser

Spotlight on the Antarctic - Friis, Erik J (The American-Scandinavian Review, 1962)
Omhandler 50 års-jubileet for Sydpolens erobring, med bl.a. overrekkelse av minneplakett, og Tore Gjelsvik til stede.
Keywords: Antarktis; Nordmenn; Norsk Polarinstitutt; Roald Amundsen; Sydpolsekspedisjonen

The Race to the South Pole - Kirwan, Laurence Patrick (The white road : a survey of polar exploration, 1959)
Keywords: Antarktis; Roald Amundsen; Sydpol; Sydpolsekspedisjonen; oppdagelsesreiser

Hitch your wagon : the story of Bernt Balchen - Knight, Clayton; Durham, Robert C (Bell, 1950)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Marking Time; Winter in the Antarctic; The Southern Cross story; The achievement of Roald Amundsen; The conquest of Antarctica by air - Nichol, J R (Stepping stones to the South Pole, 1948)
Keywords: Antarctic (skip); Antarktis; Carsten Borchgrevink; Henrik Johan Bull; Hjalmar Riiser; Kapp Adare; Larsen; Norvegia ekspedisjonene; Roald Amundsen; Southern Cross (skip); Sydpolsekspedisjonen; kartlegging; overvintring

The Attainment of the South Pole - Stefánsson, Vilhjálmur (red.) (Great adventures and explorations : from the earliest times to the present : as told by the explorers themselves, 1947)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Die Entdeckung des Südpols. Amundsen erster am Ziel - Zeidler, Paul Gerhard (Helden im ewigen Eis : im Kampf um den Nord- und Südpol, 1936)
Keywords: Antarktis; Roald Amundsen; Sydpol; Sydpolsekspedisjonen; oppdagelsesreiser

Roald Amundsen, erster am Südpol - Koll, Johannes (Der Kampf um die Pole, 1934)
Keywords: Antarktis; Roald Amundsen; Sydpol; Sydpolsekspedisjonen; oppdagelsesreiser

Amundsen conquiert le pole Sud - Gouzy, René (Dans le ciel des poles : explorations d'autrefois - d'aujourd'hui, 1931)
Keywords: Antarktis; Roald Amundsen; Sydpol; Sydpolsekspedisjonen; oppdagelsesreiser

Exploring the great continent - Taylor, Griffith (Antarctic adventure and research, 1930)
Keywords: Antarktis; Carsten Borchgrevink; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser

Sydpolsforskningens ældre Historie. Det sidste Kapløb mod Sydpolen - Ahlman, Axel; Freuchen, Peter (Kampen om Nord- og Sydpolen, 1928)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polarforskning

Wo das Südlicht flammt : Scotts letzte Südpol-Expedition und was ich dabei erlebte - Gran, Tryggve; Mohr, Adrian (Otto Uhlmann, 1928)
Publication Title: Hvor sydlyset flammer
Keywords: Antarktis; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene; reiser

Captain Amundsen's expedition, 1910-1912 - Hayes, James Gordon (Antarctica : a treatise on the southern continent, 1928)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; polarekspedisjoner

Roald Amundsen erobert den Südpol - Zeidler, Paul Gerhard (Polarfahrten : die wichtigsten Entdeckungsreisen in den Eismeeren mit Berichten der Forscher und ihrer Gefährten, 1927)
Keywords: Antarktis; Roald Amundsen; Sydpol; Sydpolsekspedisjonen; oppdagelsesreiser

Amundsen the Opportunist. The Dash for the Pole - Judd, Alfred (The conquest of the poles : and modern adventures in the world of ice, 1923)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polareksspedisjoner

Private expeditions - Borchgrevink - Gerlache - Nordenskioeld - Bruce - Drygalksi - Charcot - Filchner; Amundsen`s journey to the south pole - Markham, Clements R (The Lands of Silence : A History of Arctic and Antarctic Exploration, 1921)
Keywords: Antarktis; Carsten Borchgrevink; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; overvintring

Expedition d'Amundsen - Rouch, J (Le Pôle Sud : histoire des voyages antarctiques, 1921)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

Roald Amundsen. Der Entdecker des Südpols - Wiese, J (Entdeckingsreisen am Nord- und Südpol, 1914)
Keywords: Antarktis; Roald Amundsen; Sydpol; Sydpolsekspedisjonen; oppdagelsesreiser